Work Safety Aspects on the Sea on Small-Scale Fishermen in Jember Regency, Indonesia - Indrayani, Reny; Syamila, Ana Islamiyah; Hartanti, Ragil Ismi; Sujoso, Anita Dewi Prahastuti (Universitas Airlangga, 2023)
Introduction: The safety aspects of working on the sea which have not been properly implemented by fishermen have resulted in a high fatality rate in the fisheries sector. The dynamic conditions of the south coast sea waves in Jember Regency and the lack of understanding of safety by fishermen have caused several accidents which resulted in work fatalities. The research team viewed that the OSH problems faced by fishing communities need to be studied further. The purpose of this study was to examine the safety aspects of fishing vessels and describe the safety aspects of sailing based on individual characteristics. Method: This research is descriptive research with a quantitative approach. Respondents in this study were 260 small-scale fishermen and 24 boats. The research variables are the characteristics of the respondents and sailing safety aspects. Results: The safety aspects of fishermen are at an unsafe level with a tendency for unsafe behavior to be carried out by fishermen who have worked for more than 11 years with a working duration of more than 9 hours and most of them come from Puger Beach. Conclusion: The characteristics of Puger Beach, which has high waves with strong currents, cause many work accidents, so it needs support from the government to improve the work safety aspects of the fishermen by providing sailing safety training and appropriate PPE.